Lessons to be learned from studying Vibrio cholerae in model systems - Chaudhuri, Keya (BioMed Central, 2001)
A response to The complete genome sequence of Vibrio cholerae: a tale of two chromosomes and of two lifestyles, by Gary K Schoolnik and Fitnat H Yildiz, Genome Biology 2000 1:reviews1016.1-1016.3.